2017
DOI: 10.1007/s11011-017-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral viral challenge triggers hippocampal production of inflammatory proteins

Abstract: Peripheral viral infections increase seizure propensity and intensity in susceptible individuals. We have modeled this comorbidity by demonstrating that intraperitoneal (ip) injection of the conventional viral mimetic, polyinosinic-polycytidylic acid (PIC), renders the brain hypersusceptible to seizures induced by kainic acid (KA). At the molecular level, the hippocampus, which is the ictal site of KA-induced seizures, exhibits upregulated expression of messages encoding several inflammatory genes. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We have previously shown that PIC challenge robustly upregulates cerebral expression of the Cxcl10 gene at the message Michalovicz and Konat, 2014) and protein (Petrisko and Konat, 2017) levels. Here, we found neurons to be the predominant cell type responsible for CXCL10 generation in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that PIC challenge robustly upregulates cerebral expression of the Cxcl10 gene at the message Michalovicz and Konat, 2014) and protein (Petrisko and Konat, 2017) levels. Here, we found neurons to be the predominant cell type responsible for CXCL10 generation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Eight-week old female C57BL/6J mice obtained from Charles River Laboratories (Wilmington, MA) were housed with free access to food and water in a humidity-and temperaturecontrolled rooms under a 12:12 h light-dark cycle. Female mice were used to be consistent with previous studies (Kirschman et al, 2011;Michalovicz and Konat, 2014;Hunsberger et al, 2016Hunsberger et al, , 2017Petrisko and Konat, 2017). Mice in all experimental groups were matched by weight prior to treatments.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations